LEVEL OF UNDERSTANDING AND READINESS OF ACADEMIC COMMUNITY IN MBKM IMPLEMENTATION AT MUHAMMADIYAH UNIVERSITY OF JAKARTA - Bahar, Herwina; Nuraeni, Nuraeni; Ismah, Ismah; Herli, Venni; M, Aby; Rosiyanti, Hastri; Setiyanti, Anis; Izzah, Lidiyatul; Widyasari, Nurbaiti (Dinasti Publisher, 2022)
The purpose of this research is to find out the level of understanding and readiness of the academic community of the University of Muhammadiyah Jakarta in the implementation of the Merdeka Belajar Kampus Merdeka (MBKM) program. The research method used is quantitative derivative, the object of research/respondents who are sampled are lecturers, students, and education personnel. Data retrieval technique by filling out questionnaires through SpadaDikti survey link. The results of the analysis of questionnaire data are interpreted in the form of percentages of each answer given by respondents. The results of this research can be a reference material for further research, in the implementation of the MBKM Program implemented at the University of Muhammadiyah Jakarta, so that it is expected to improve and improve the performance of the Merdeka Belajar Kampus Merdeka (MBKM) program.